Modelling of energy expenditure at welding workstations: effect of temperature on work performance (2008)
The welding workstation usually generates intense heat during operations, which may affect the welder's health if not properly controlled, and can also affect the performance of the welder at work. Consequently, effort to control the conditions of the welding workstation is essential, and is therefore pursued in this paper. This paper develops a mathematical model that maximises the work output while minimizing energy consumption at the welding workstation. Particular emphasis is placed on the effect of temperature on work performance. The important principle of conduction is applied through the human flesh that experiences temperature changes at the welding workstation. The welder-environment interaction is investigated with a focus on the welder's link and their relationship with blood flow. The results show that the blood in the arteries loses heat to the blood in the veins, and is aided by convection in the veins, Further heat losses occur in the skin layer of fat and muscle, and finally to the air. The study hopes to stimulate greater productivity and optimised resource utilisation. Thus, the Safety, Health and Environment (SHE) manager can assist in controlling the surroundings for optimal welder's comfort.